2023
DOI: 10.1186/s12891-022-05944-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the six-minute walk test performed over a 15 and 30 m course by children with cerebral palsy

Abstract: Background The aim of this study was to compare performance on the six-minute walk test (6MWT) performed over 15 m and 30 m courses by children and youths with cerebral palsy (CP). Methods Children and youths with CP at Gross Motor Function Classification System levels I–IV performed the 6MWT in a straight 15 m-long corridor (first trial) and 30 m-long corridor (second trial). The intraclass correlation coefficient (ICC) and Bland-Altman plots were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Likewise, study findings for interrater reliability are consistent with those reported by other investigations that included older adults without disabilities [ 17 , 18 ]. Regarding modifications to the conventional 6MWT, a previous study had children with CP perform the 6MWT over 15 and 30 m courses [ 67 ]. The authors concluded that a shorter and narrower walking course could result in more turning and less straight walking paths, both of which could negatively affect or add volatility to the walking distances [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, study findings for interrater reliability are consistent with those reported by other investigations that included older adults without disabilities [ 17 , 18 ]. Regarding modifications to the conventional 6MWT, a previous study had children with CP perform the 6MWT over 15 and 30 m courses [ 67 ]. The authors concluded that a shorter and narrower walking course could result in more turning and less straight walking paths, both of which could negatively affect or add volatility to the walking distances [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding modifications to the conventional 6MWT, a previous study had children with CP perform the 6MWT over 15 and 30 m courses [ 67 ]. The authors concluded that a shorter and narrower walking course could result in more turning and less straight walking paths, both of which could negatively affect or add volatility to the walking distances [ 67 ]. This could explain the variable differences observed between the HM6MWT and 6MWT distance results in our study.…”
Section: Discussionmentioning
confidence: 99%